Explaining the Intention–Actual Use Gap in Mobile JKN Online Queues through Behavioral Intention Mediation - Dwi Puspitasari Anggita Anggraeni; Duta Liana; Ratna Indrawati (Harmony Management: International Journal of Management Science and Business, 2026)
Digital transformation in healthcare services is a strategic approach to improve access, efficiency, and service quality, particularly within Indonesia’s National Health Insurance (JKN) system. BPJS Kesehatan has introduced an online queue feature through the Mobile JKN application to minimize manual queuing and reduce waiting times in outpatient services. However, despite the widespread ownership of the application, its actual utilization for online queuing remains relatively low, including in a regional public hospital (RSUD) in West Bandung. This condition reflects a gap between the availability of digital health technology and patients’ actual usage behavior, highlighting the need to examine factors influencing adoption.This study aims to analyze the effects of perceived ease of use, social influence, and facilitating conditions on the actual use of the Mobile JKN online queue, with behavioral intention as an intervening variable among outpatients. A quantitative cross-sectional design was applied, involving 255 JKN outpatient participants selected through purposive sampling. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS version 24, based on the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). Data analysis included descriptive statistics, validity and reliability testing, normality assessment, goodness-of-fit evaluation, Three Box Method, and hypothesis testing.